Study of Intersection Coverage Area for Pedestrian Overpasses as Vertical Evacuation from Tsunami in Padang, West Sumatra - Syukri, Andi (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2018)
Padang City, as one of the highest vulnerable from earthquake and tsunami, has been transforming to become disaster smart city. However, the inadequacy of horizontal evacuation routes is caused by numerous tremors in 2007, 2009, 2010, and 2016 are indicating it is lack of occupancy for evacuee. Then, these condition is decreasing by traditional behavior evacuee are still using the vehicle and unwell planned evacuation as personally or in the community. The small number of vertical evacuation building and lack of awareness of community, and unmanaged the evacuation facilities make emergency response from earthquake and tsunami is uncontrolled in 0 – 20 minute for 30 minutes remaining time evacuate to inland in personally or community. Padang city has people density in the more than 1,317 people/km2 in the coastal area numerous potential for earthquake and tsunami risk. Pedestrian overpasses as primary facilities in many main roads in Padang City should be utilized for people to cross the road but it does not work properly but in fact, type of material, steel construction, was not durable with the climate in Padang that have coastal climate and a high number of behavior for crossing road in uncertain places. Regarding of the vulnerability in earthquake and tsunami risk, unmanaged construction and bad culture in crossing the road, pedestrian overpasses, especially in the intersection, will be redesigned to be a vertical evacuation. It will have a multifunction structure that is not simply for passing the pedestrian but also comprises remarkable facilities as a meeting point, commercial place and public facilities. Pedestrian overpasses for vertical evacuation from the tsunami will solve lack of area for construct vertical evacuation in the community. It can duplicate easily for any coastal cities that require vertical evacuation structures. Apparently, area availability will determine how vulnerable the site for vertical evacuation will suit for evacuee who living surrounding. Road intersection will be a good site for redesigning vertical evacuation Intersection of the road and have large space will be a good candidate for redesigning pedestrian overpasses as vertical evacuation structure. Road Intersection as vulnerable routes for horizontal evacuation is already happened in several occurrence of earthquake in Padang City. Based on google maps, every road will contribute a number of evacuee and mostly by using vehicle and fewer people who will evacuate by walking. The Study of coverage area intersection pedestrian overpasses as vertical evacuation from tsunami in Padang, West Sumatra will describe about how large the estimated capacity of pedestrian overpasses can be suit for vertical evacuation and how wide the area can be facilitated by this evacuation site. Remaining time of tsunami, walking space, readiness evacuation time, and time to reach upland. Those will be determined into how far the evacuee can reach the site. Based on the population density, it can observed the length of the radius can be serviced the evacuee to evacuation structure. People density will influence how large the coverage area for each site. According to this study, horizontal evacuation from tsunami in Padang city is still vulnerable for the people who living in coastal area. Bottleneck evacuation can be solved by build a vertical evacuation near by the bottleneck zone. Pedestrian overpasses for vertical evacuation is designing to accommodate the evacuee can save their life from the tsunami run up because incapability to reach inland.